English Diphthong Pronunciation: A Quantitative Evidence of Articulatory Difficulties Among EFL Learners - Anggun Angriani; Konder Manurung; Hastini Hastini (Journal of English Language and Education, 2026)
This study investigated students’ difficulties in pronouncing English diphthongs and the factors contributing to those difficulties among second-semester students of the English Education Study Program at Tadulako University. A quantitative descriptive design was employed. Data were collected through a pronunciation test and a questionnaire. The pronunciation test was used to identify students’ ability in pronouncing English diphthongs, while the questionnaire examined factors affecting their pronunciation difficulties. The findings revealed that students experienced varying levels of difficulty in producing English diphthongs, particularly in maintaining smooth vowel glides and accurate articulatory movements. Several students tended to simplify diphthongs into monophthongs or produce incomplete vowel transitions, reflecting the influence of their first language. Questionnaire results showed that learning environment was the most influential factor (M = 3.12), followed by articulatory difficulty (M = 2.95) and learning media (M = 2.90), all categorized as high-level factors. Teaching materials were perceived as moderately influential, with mean scores of 2.68 and 2.79. These findings indicate that students’ pronunciation difficulties are influenced by a combination of articulatory complexity, first-language interference, learning conditions, instructional resources, and limited opportunities for pronunciation practice. Overall, the study highlights the importance of creating supportive learning environments and providing systematic pronunciation instruction to improve EFL learners’ mastery of English diphthongs.